Evaluation of the Deworming Medication Program for School-Aged Children in Simpang IV Sipin Public Health Center - Wisudariani, Evy; Wulansari, Arnati; Hidayat, Ahmad Thohir; Asty, Zahra Frizki (Jurnal Kesmas Jambi, 2025)
Neglected Tropical Diseases (NTDs) remain a public health concern in Indonesia. STH infections are among the neglected tropical diseases that continue to pose a significant public health problem, particularly in areas with poor sanitation and low levels of hygiene. School-aged children (5–14 years) are especially vulnerable, as they are often exposed to environments contaminated with parasitic worm eggs. The objective of this study is to evaluate the implementation and effectiveness of the deworming program and to formulate improvement recommendations. Qualitative research design using evaluation model approach (input, process, output, and outcome) was employed. Data collection techniques were carried out by indepth interviews, document review and observation. Validity test of data was done using triangulation source, method, and theory. Data processing was descriptively. The program officer responsible for the deworming program at Simpang IV Sipin PHC has a background in a three-year Diploma of Midwifery and has 15 years of work experience. It is noted that the officer has never received any specific training related to this program. The program coverage and achievement targets have been fully attained, with the number of children receiving deworming medication meeting the established goals. There is a persistent deficiency in the conduct of regular monitoring and evaluation. Simpang IV Sipin Primary Health Center should strengthen coordination with schools to ensure timely implementation of the preventive deworming schedule, conduct systematic monitoring and evaluation to maintain high program coverage and adherence to medication, and provide age-appropriate educational materials to enhance children’s awareness of helminth infection prevention.